2020
DOI: 10.3174/ajnr.a6360
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Wall Thickening and Enhancement in High-Resolution Intracranial Vessel Wall Imaging: A Predictor of Future Ischemic Events in Moyamoya Disease

Abstract: BACKGROUND AND PURPOSE: Very few data are available with regard to high-resolution intracranial vessel wall imaging characteristics of Moyamoya disease and their relation to ischemic stroke risk. We investigated the high resolution imaging characteristics of MMD and its correlation with recent ischemic events. MATERIALS AND METHODS:Patients with Moyamoya disease confirmed by DSA, including patients after revascularization, were enrolled. All the patients underwent high-resolution intracranial vessel wall imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
0
28
2
Order By: Relevance
“…Despite this being the first reported case of vessel wall enhancement in PHACE syndrome, other similar arterial pathologies have documented vessel wall enhancement, supporting our findings. For example, enhancement has been seen in cases of other causes of secondary MMV, 12 idiopathic moyamoya disease, 13 14 both paediatric 15 and adult AIS, 16 17 and multiple types of vasculitides. 18 19 Specifically, in the paediatric population, the Vascular Effects of Infection in Pediatric Stroke Study was the largest study evaluating stroke in the paediatric population, prospectively enrolling 355 children with arterial ischaemic stroke (2010–2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this being the first reported case of vessel wall enhancement in PHACE syndrome, other similar arterial pathologies have documented vessel wall enhancement, supporting our findings. For example, enhancement has been seen in cases of other causes of secondary MMV, 12 idiopathic moyamoya disease, 13 14 both paediatric 15 and adult AIS, 16 17 and multiple types of vasculitides. 18 19 Specifically, in the paediatric population, the Vascular Effects of Infection in Pediatric Stroke Study was the largest study evaluating stroke in the paediatric population, prospectively enrolling 355 children with arterial ischaemic stroke (2010–2014).…”
Section: Discussionmentioning
confidence: 99%
“…Strong enhancement of the intracranial vessel wall was found to be associated with the progression of intracranial artery stenosis, while a lack of enhancement was associated with stability of intracranial artery stenosis [34]. As a clinical relevance, the presence of contrast enhancement and wall thickening showed a statistically significant association with ischemic events [35]. It has also been suggested that the modality of blood flow evaluation suggests an underlying condition for the ischemic onset.…”
Section: Clinical Factors Associated With Ischemic Onset Moyamoya Diseasementioning
confidence: 99%
“…Compared with IAS, the outer diameters of stenotic ICA and MCA are smaller in patients with MMD. High-grade arterial wall enhancement on IVWI may associate with the progression of angiopathy and a high risk of ischemic infarction [30,58]. However, the difference in vessel wall enhancement between early and late angiographic stages of MMD remains to be further investigated [47].…”
Section: Intracranial Vessel Wall Imaging (Ivwi)mentioning
confidence: 99%